Self-foamed biosystem for deep reservoir conformance control - Suleimanov, Baghir A.; Rzayeva, Sabina J.; Akberova, Aygun F.; Akhmedova, Ulviyya T. (Petroleum science and technology, 2022)
The goal of this research is to develop formulations for blocking highly permeable zones using cheap, traditional reagents and materials, and to determine the dependence of the position of the blocking screen on the degree of watering of the oil formation in order to maximize the efficiency of oil displacement. Using readily available chemical reagents and biosystems, technology for generating a stable foam system with adjustable rheological properties and providing deep alignment of the displacement front has been developed. In the study, the required penetration depth of the proposed foam system to achieve the maximum effect at different water cuttings was determined; moreover, the effect of pressure on the stability of the foam system generated as a result of decomposition of the biosystem was studied, and the significant effect of gas saturation on the rheology of the foam system was confirmed. It was further established that with a high water-cut (more than 90%), isolation was most effective in the production wells. At a 50% water cut, the deep diversion of the injected fluid gave promising results, however, the best results were achieved using isolation near the discharge line immediately after the water breakthrough in the production wells.